Ammonium and guanidine carbosilane dendrimers and dendrons as microbicides. (April 2018) - Heredero-Bermejo, Irene; Hernández-Ros, José M.; Sánchez-García, Leticia; Maly, Marek; Verdú-Expósito, Cristina; Soliveri, Juan; Javier de la Mata, F.; Copa-Patiño, José L.; Pérez-Serrano, Jorge; Sánchez-Nieves, Javier; Gómez, Rafael
Graphical abstract: Highlights: Ammonium carbosilane dendritic systems are easily obtained by thiol-ene addition. Guanidine derivatives are easily obtained by nucleophilic substitution. Low generation dendritic systems are the most active as microbicides. Low generation dendritic systems are the least cytotoxic compounds. Modelling of dendrimer/membrane interactions helps to understand activity. Abstract: Carbosilane dendrimers (generations 1–3) and dendrons (generations 2–3) functionalized with guanidine functions (GU) have been synthesized from corresponding ammonium (–NH3 + ) derivatives with good yield. These dendritic molecules were tested as microbicides against Escherichia coli (Gram-negative), Staphylococcus aureus (Gram-positive) and methicillin resistant S. aureus (MRSA) bacteria; and against Acanthomoeba polyphaga in both stages, trophozoites and cysts. The best results were obtained for lower generation dendrimers and dendrons, with no remarkable influence of the peripheral moieties against bacteria but with better amoebicide activity for –NH3 + systems. Moreover, the activity values of first generation dendrimers and second generation dendrons were below their cytotoxicity against eukaryote cells. Molecular dynamics study of interactions between selected dendrimers and anionic phospholipid bilayers indicates possible connections between the antibacterial activity and interaction modes.